Childhood leukaemia, nuclear sites, and population mixing. - Kinlen, L (2011)
The excess of childhood leukaemia (CL) in Seascale, near the Sellafield nuclear reprocessing site in rural NW England, suggested that an epidemic of an underlying infection, to which CL is a rare response, is promoted by marked population mixing (PM) in rural areas, in which the prevalence of susceptibles is higher than average. This hypothesis has been confirmed by 12 studies in non-radiation situations. Of the five established CL excesses near nuclear sites, four are associated with significant PM; in the fifth, the Krummel power station in Germany, the subject has not been thoroughly investigated.